KESEJAHTERAAN PSIKOLOGIS DITINJAU DARI EFIKASI DIRI DAN KECERDASAN EMOSI REMAJA AWAL - , PERMATA ASHFI RAIHANA, Murtini, SU. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The present study aimed to investigate the correlation of self-efficacy and emotional intelligence on psychological well-being of early adolescence. It made used of cluster random sampling in selecting 90 early adolescence from SMP N X RSBI Surakarta. This study sample responded to three instruments